Production of charmed pseudoscalar mesons in antiproton-proton annihilation - Haidenbauer, J.; Krein, G. [UNESP] (Amer Physical Soc, 2014)
We study the production of charmed mesons (D, D-s) in antiproton-proton ((p) over barp) annihilation close to the reaction thresholds. The elementary charm production process is described by baryon exchange and in the constituent quark model. Effects of the interactions in the initial and final states are taken into account rigorously. The calculations are performed in close analogy to our earlier study on (p) over barp -> (K) over barK by connecting the processes via SU(4) flavor symmetry. Our predictions for the D (D) over bar production cross section are in the order of 10(-2) - 10(-1) mu b. They turned out to be comparable to those obtained in other studies. The cross section for a Ds+Ds- pair is found to be of the same order of magnitude despite the fact that its production in (p) over barp scattering requires a two-step process.